Asynchronous flowering patterns in saguaro cacti (Carnegiea gigantea). Issue 12 (12th December 2021) - Foley, Theresa; Swann, Don E.; Sotelo, Guadalupe; Perkins, Nicholas; Winkler, Daniel E.
Abstract: The saguaro cactus ( Carnegiea gigantea [Engelm.] Britton & Rose) is a keystone species endemic to the Sonoran Desert of northern Mexico and the southwestern United States. The saguaro produces large white flowers near its stem apex (crown) during April–June, which bloom at night and close the following day. In 1924, Duncan Johnson reported that saguaro floral buds are likely to have an asymmetrical distribution in which buds occur in higher densities on the eastern half of a plant's crown. Using technology not available to Johnson, we tested his observations to determine whether flowers are asymmetrically distributed using repeat photography. We also tested whether there is a seasonal pattern of flowering that may explain Johnson's observations. We tracked intra‐individual flowering phenology of 20 saguaros and measured 2372 flowers across two reproductive seasons in Saguaro National Park, Tucson, Arizona. Flowers first appeared on the east side of all saguaro crowns at the start of the reproductive season, and then spread radially in a counterclockwise direction as the season progressed. In contrast to previous reports, saguaro flowers were consistently more abundant on the northern part of the crown than in the eastern part. To our knowledge, this study is the first to document a seasonal, counterclockwise pattern of asynchronous flowering in saguaro or any angiosperm. We discuss potential drivers of this phenomenon as well as implications for saguaros responding to climate change.